Histological and Immunohistochemical Characterization of a Case of Endometriosis in a Guinea Pig (Cavia tschudii) - Alfonso Baldi; Andrea Lanza; Francesco Menicagli; Pietro G. Signorile; Enrico P. Spugnini (Case Reports in Veterinary Medicine)
Endometriosis is a chronic gynecological disease characterized by the ectopic proliferation of endometrial tissue outside of the uterine cavity. The pathogenesis of this disease is still obscure, and Sampson’s theory of retrograde menstruation is still the most widely accepted explanation. Endometriosis in animals has been so far described not only in baboons and a rhesus macaque but also in dogs and horses that are nonmenstruating animals. In this article, we report the histological and immunohistochemical characterization of the first case of ovarian cystic endometriosis and adenomyosis in a guinea pig. The case presented supports the hypothesis that endometriosis is a disease not at all related to the phenomenon of retrograde menstruation but is a consequence of some alterations in the morphogenesis of the female genital system and therefore it could be found in any mammal. We suggest considering endometriosis among the other pathological phenotypes in animals displaying ovarian and uterine alterations and having a history of difficulties in conceiving.